Painting of Vishnu sitting on an Elephant - Temples of India Project Team (Jio Institute, 2024)
Closer view of one of the paintings that frame the side doorways on the mandapa (pillared hall) of the Bhandasar Temple. Seen here is the painting of Vishnu sitting on an elephant. A mahut (charioteer of the elephant) is shown riding it in the city. The elephant has multiple trunks. The jewellery worn by Vishnu, the elephant and the canopy, in which Vishnu is shown sitting on the elephant's back, are embossed with gold.